DEBT POLICY, EFFICIENCY RATIO, PROFITABILITY, AND SYSTEMATIC RISK: EVIDENCE FROM INDONESIA - Bram Hadianto; Herlina Herlina; Rosemarie Sutjiati Njotoprajitno (Owner : Riset dan Jurnal Akuntansi, 2023)
Systematic risk is relevant for investors in the stock transaction because portfolio creation cannot eliminate it. Thus, the influencing factors need to be recognized since the managers attempt to elevate the company value in the capital market, and this research exists to identify them. By denoting the previous research evidence, at least three determinants are available, i.e., debt policy, efficiency ratio, and profitability. The population comes from the consistent non-financial companies selected from the Kompas 100 index constituents in the Indonesian capital market between 2014 and 2019, where their total is 46. Moreover, the Slovin formula counts the samples with a fault boundary of 10%. Based on this formula, their sum is 32 companies, grabbed by a simple random sampling technique. Then, to analyze the data, this study applies the regression model with pooling data: the combination of time series and cross-sectional features. After testing the data, this investigation finds that the debt policy positively affects this risk; however, efficiency and profitability ratios negatively influence this risk. It implies that despite potential bankruptcy leading to higher systematic risk, the debt can effectively push the managers to use the cash flow for the necessary spending, resulting in revenue and profitability, despite taking on risky projects.